Thematic Analysis in Physics Text Entitiled “Energy Can Neither Be Created Nor Destroyed” - Edi Suprayetno (LingPoet: Journal of Linguistics and Literary Research, 2020)
Departing from systemic functional linguistics theory, this study is aimed at analyzing textual function found in physics text entitled “Energy Can Neither Be Created Nor Destroyed” . This study used descriptive qualitative method. The data were in the form of clauses totaling to 28 clauses from 8 paragraphs. From the result of the analysis, it was found that marked and unmarked Theme were realized in the data. Then, the dominant Theme found which reaches 20 Themes from the 28 Themes found or it is equal to 71,42%. It can be interpreted that the text use common structure in the clause.